Allometric Expression of Sesame Cultivars in Response to Various Environments and Nutrition - Meer Muhammad Khan (MDPI AG, 2021)
Sesame cultivars perform differently in various environments comprising specific locations and years. Micronutrient fertilizers increase crop yields and can enhance resistance to environmental hazards and contribute to potential yield. For assessing the effect of environment and micronutrients, field experiments were carried out at three different locations (BARI, URF and NARC) of Pothwar region, Pakistan, in two succeeding years (2014, 2015). Four sesame cultivars and three micronutrients (Zn, B and Mn) with a control treatment were used in RCB design with a split-plot procedure and four replications. The results showed significant differences in the main effects of all tested factors (cultivars, micronutrients, locations and years). Maximum mean values of plant height, capsules plant−1, biomass yield and seed yield were recorded for SG-30, while TH-6 was the lowest for these parameters. Maximum mean values of capsule length, capsule weight, seeds capsules−1 and the weight of 1000 seeds were recorded for TH-6 but vice versa for SG-30. Maximum capsule length and seeds capsule−1 were observed at NARC, while other growth and yield attributes were maximum at BARI and URF, including biomass yield and seed yield. The interactive effect of cultivar × location × year was highly significant for all growth and yield traits except capsule length. Sesame cultivars revealed a differential response for all traits at three locations during both years. Application of micronutrients significantly augmented all growth and yield features of sesame. Micronutrient fertilizers (i.e., ZnSO4 at 10 kg ha−1, borax at 10 kg ha−1 and MnSO4 at 5 kg ha−1) would increase yield and yield-attributing traits in low- or medium-precipitation areas where suitable cultivars have been designated.